(untitled) (World Conference on Agricultural and Earth Sciences, 2026)
Effective board governance and corporate transparency are essential components of sound corporate management and sustainable business development. In Uzbekistan, ongoing economic reforms and efforts to modernize the corporate sector have increased the importance of strengthening oversight mechanisms within joint-stock companies. This article examines the role of board governance and corporate transparency in improving managerial oversight and enhancing overall corporate effectiveness. The study proposes a management framework that integrates board responsibilities, transparency practices, and accountability mechanisms to support effective oversight. Using analytical and conceptual approaches, the research evaluates existing governance challenges, including limited board independence, information asymmetry, and inconsistent disclosure practices. The findings suggest that strengthening board governance structures and improving transparency can significantly enhance decision-making quality, reduce governance risks, and increase investor confidence. The proposed management framework emphasizes the strategic role of boards in monitoring management performance, ensuring transparent information flows, and aligning corporate activities with long-term organizational objectives. The article concludes that improving board governance and corporate transparency is a critical prerequisite for effective oversight and sustainable corporate development in Uzbekistan.